MEMPELAJARI BERBAGAI FORMULASI EKSTRAK KUNYIT DAN ASAM (CURCUMA DOMESTICA VAL.- TAMARINDUS INDICA L.) TERHADAP AKTIVITAS ANTIOKSIDAN - Wrasiati Ari Prihantini Lestari, Luh Putu (Agrotekno; Vol. 14, No. 1 Februari 2008)
The purpose of thus research were to find out the formulation of extract of curcumin and tamarind leaves which had an optimum antioxidant activity. The observations were undertaken on the phenol values, radical scavenging activity, antioxidant activity test with FTC method, antioxidant activity test with TBA method, water content, and pH. The result showed that the formulation of curcumin and tamarind leaves had influence to the phenol values and the radical scavenging activity. Addition of curcumin and tamarind extract in FTC and TBA methods showed that the formula was successful to purpose lipid oxidation. The highest phenol value (18.51%) was found in R9 which consisted of 20% curcumin extract and 80% of tamarind leaves extract, meanwhile the phenol value of 100% tamarind leaves extract was 9.05%, and the phenol value if 100% tamarind leaves extract was 5.34%. The highest radical scavenging activity (0.27%) was found in R8 which consisted of 30% curcumin extract and 70% of tamarind leaves extract, meanwhile radical scavenging activity of 100% curcumin extract was 0.17% abd the 100% tamarind leaves was 0.23%.
Keywords: Curcumin, tamarind, extract, antioxidant